Artikel Analisis Kadar Tanin Ekstrak Metanol Bunga Telang (Clitoria ternatea L.) dengan Metode Spektrofotometri UV-Vis - Sana Nurul Khasanah; Sutaryono; Qory Addin (Universitas Muhammadiyah Klaten, 2021)
Telang flower (Clitoria ternatea L) has many benefits for humans in terms of medicine. Telang flower (Clitoria ternatea L) is efficacious for treating bronchitis, red eyes, throat, skin diseases, urinary disorders and anti-toxins. Telang flower has tannin compounds that function as antioxidants and antimicrobials. The purpose of this study was to determine the tannin content of the telang flower (Clitoria ternatea L) using the UV-Vis Spectrophotometry method. The research method used is observational. The population in this study was the telang flower (Clitoria ternatea L), the telang flower was extracted using the maceration method with 70% methanol as solvent. Quantitatively analyzed using UV-Vis Spectrophotometry method. The results showed that the quantitative test using UV-Vis Spectrophotometry at a wavelength of 753.5 nm with an absorbance of 1,352. The standard curve for gallic acid is y = 0.0085x – 0.0835, the value of r = 0.9912. The average tannin content obtained is 1.611% (w/w).